Innovations in rural and agriculture finance - Kloeppinger-Todd, Renate; Sharma, Manohar (International Food Policy Research Institute, 2010)
Most rural households lack access to reliable and affordable finance for agriculture and other livelihood activities. Many small farmers live in remote areas where retail banking is limited and production risks are high. The recent financial crisis has made the provision of credit even tighter and the need to explore innovative approaches to rural and agricultural finance even more urgent. This set of 14 briefs clearly points out the importance of business realities faced by small farmers, including low education levels, the dominance of subsistence farming, and the lack of access to modern financial instruments. Innovations in rural and agriculture finance: Overview Renate Kloeppinger-Todd and Manohar Sharma; Financial literacy Monique Cohen; Community-based financial organizations: Access to Finance for the Poorest Anne Ritchie; Rural banking in Africa: The Rabobank approach Gerard van Empel; Rural banking: The case of rural and community banks in Ghana Ajai Nair and Azeb Fissha; Rural leasing: An alternative to loans in financing income-producing assets Ajai Nair; Determinants of microcredit repayment in federations of Indian self-help groups Yanyan Liu and Klaus Deininger; M-PESA: Finding new ways to serve the unbanked in Kenya Susie Lonie; Biometric technology in rural credit markets: The case of Malawi Xavier Giné; Credit risk management in financing agriculture Mark D. Wenner; New approaches for index insurance: ENSO insurance in Peru Jerry R. Skees and Benjamin Collier; Microinsurance innovations in rural finance Martina Wiedmaier-Pfister and Brigitte Klein; Combining extension services with agricultural credit: The experience of BASIX India Vijay Mahajan and K. Vasumathi; Bundling development services with agricultural finance: The experience of DrumNet Jonathan Campaigne and Tom Rausch